Relationship between Perceived Stress, Locus of Control and Psychological Wellbeing among Medical Students - Mustafa, Sana; Umar, Samreen; Mustafa, Iman; Atta, Mohsin (Pakistan Journal of Humanities and Social Sciences, 2024)
The medical profession is widely acknowledged as one of the most stressful, with medical students frequently experiencing heightened stress that can negatively affect their psychological health. This study aimed to explore the association between perceived stress on locus of control, and psychological well-being. Locus of control was defined exclusively as the internal locus of control. A total of 193 medical students, including 150 men and 43 women, aged 18-25 (M = 22.21, SD = 2.91), participated in this research, which employed a correlational research design and purposive sampling methods. The correlational analysis revealed a strong negative correlation between perceived stress and psychological well-being. Additionally, a significant negative relationship was found between perceived stress and internal locus of control. Psychological well-being, in turn, showed a strong positive correlation with internal locus of control. The study further found that perceived stress significantly and negatively impacted both internal locus of control and psychological well-being. The study also addresses its limitations and offers recommendations for improving the well-being of medical students, such as engaging in stress-reducing activities, practicing deep breathing, progressive muscle relaxation, and seeking therapy to manage stress.